Mapping the National Insight of the Salafi Group in Indonesia Based on their Fatwa on Social Media - Ridha DS, Muhammad; Afridawati, Afridawati; Iskandar, Nuzul; Mursal, Mursal (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article provides an overview of the national insight of the Salafi group as reflected in the lectures of their figures on the YouTube platform about saluting the flag. The aim is to enrich insight into the Salafi group in Indonesia, which is often seen from only one perspective. This study uses qualitative data with a discourse analysis approach within the framework of the study of ushūl fiqh. Discourse analysis is used to examine the statements of the preachers semantically, social cognition, and social context, while ushūl fiqh analysis is used to see their legal reasoning. Data were collected using documentation techniques from videos of lectures by Salafi preachers on digital platforms that can be used as an important space to understand their national insight. This study reveals that all Salafi preachers in Indonesia are allowed to salute the flag because this theme does not fall within the realm of faith. However, they do not recommend it to be done. This attitude is different from non-Salafi preachers who advocate it because the red and white flag is part of the struggle of Islamic scholars and Muslims. Regarding legal reasoning in fiqh, these preachers try to enter the khilāfiyah fiqh (a matter of differing opinions) space and choose an opinion that allows saluting the flag. This tendency then received a positive response from the majority of netizens. This study concludes that the Salafi group in Indonesia has used an adaptation strategy approach by utilizing rhetorical skills to avoid anti-nationalism stigma.